Too much of a good thing? The moderating role of children’s perceived social support in drawing activities - Taiyu Nie; Kuan-Chun Tsai; Jun Wu (PLoS ONE, 2026)
Art engagement plays a crucial role in children’s flourishing, yet there is limited understanding of how individual traits and environmental factors shape children’s art engagement. Drawing on Cognitive Evaluation Theory (CET), this study examines the relationship between children’s drawing self-efficacy and art engagement, as well as the moderating role of perceived social support. A cross-sectional survey was conducted with 592 children aged 10–12 in Henan Province, China, using paper-based questionnaires. The results indicated that both drawing self-efficacy and perceived social support positively predicted art engagement; however, high levels of perceived social support weakened the positive relationship between drawing self-efficacy and art engagement. These findings challenge the common assumption that social support is uniformly beneficial and highlight the importance of autonomy-supportive practices. The key challenge lies in providing support that strengthens children’s autonomy in drawing activities. Parents and art educators should therefore adopt autonomy-supportive approaches to help children remain actively engaged in drawing activities and achieve long-term developmental benefits.